Achieving Environmentally Responsible Behavior for Tourists and Residents: A Norm Activation Theory Perspective. (July 2021) - Confente, Ilenia; Scarpi, Daniele
Applying Norm Activation Theory to tourism, this study develops a conceptual model for both tourists and residents starting from their awareness of the negative environmental consequences of tourism, addressing ascription of responsibility, environmental sensitivity, place attachment, and environmentally responsible behavior. This research shows that ascription of responsibility mediates the relationship between awareness of negative consequences and that environmentally responsible behavior and environmental sensitivity and place attachment moderate the mediation. Consequently, developing awareness of the consequences of tourism is important to developing strong responsibility ascription and environmentally responsible behavior. The model is split to compare residents and tourists, and systematic differences in the path estimates emerge for the two groups. Furthermore, different types of tourists are compared, revealing that awareness of the negative environmental consequences of tourism and ascription of responsibility are unvaried for new and experienced tourists, but that tourists' visit length significantly affects both awareness and place attachment.